PENANAMAN NILAI KARAKTER CINTA TANAH AIR PADA PESERTA DIDIK DI SD SWASTA HOSANA MEDAN DELI - Frengki Pangaribuan; Yakobus Ndona; Daulat Saragi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the instillation of patriotism character values ​​in students of Hosana Private Elementary School, Medan Deli. The method used is qualitative with a descriptive approach, with data sources including the principal, teachers, students, and related documents. Data were collected through observations of school activities, in-depth interviews, and documentation, then tested for validity by triangulating sources and analyzed through reduction, presentation, and drawing conclusions. The results of the study indicate that patriotism values ​​are instilled through intracurricular, co-curricular, and extracurricular activities, with the support of the active role of teachers, a conducive school culture, and student involvement in activities based on local culture and nationalism.